Aqueous Rechargeable Multivalent Metal‐Ion Batteries: Advances and Challenges. Issue 24 (12th May 2021) - Pan, Zhenghui; Liu, Ximeng; Yang, Jie; Li, Xin; Liu, Zhaolin; Loh, Xian Jun; Wang, John
Abstract: Aqueous rechargeable multivalent metal‐ion batteries (ARMMBs) have a great potential to meet the future demands in the wide spectrum of energy storage applications, ranging from wearables/portables to large‐scale stationary energy storage. This is owing to the abundance of the electrode materials, their eco‐friendliness, high safety, fast‐charging capability, high power density, and long‐cycling capability. There has been considerable progress in ARMMBs over the past ten years. However, their rather narrow operating voltage window and insufficient energy density are still the main barriers to their use as alternative power sources to replace the widely used lithium‐ion batteries. In this overview, the key advantages and current challenges for ARMMBs with respect to the cathode materials, electrolytes, metal anodes, and their integrations into full cells are first examined. The recent approaches in addressing these key challenges are then looked into, focusing on the new designs of advanced electrode materials, electrolytes, and also their interfaces. Finally, perspectives on the near‐future development of ARMMBs are presented, together with a brief roadmap, where one of main pursuits will be to translate ARMMBs from current laboratory prototypes to commercialization/industrialization. Abstract : This review first examines the key advantages and current challenges for aqueous rechargeable multivalent metal‐ion batteries with respect to the cathode materials, electrolytes, metal anodes, and their integration into full cells. The recent approaches in addressing these key challenges are then looked into, focusing on the new designs of advanced electrode materials, electrolytes, and also their interfaces.